Investigation of cilia-associated kinesin families - Littledale, Charles (2018)
Kinesins are a protein superfamily that function via microtubules by converting energy released from ATP hydrolysis into mechanical work. Kinesins have been classified into 14 families; the distribution of which can highlight potential roles of the family members. Kinesin-16s are found solely in organisms that build cilia/flagella, whilst Kinesin-13s are only absent in organisms that do not build cilia. The Kinesin-13 family is comprised of three subfamilies. Both 13A and 13B have motors involved in ciliary function, but the roles of 13C are still unknown. The purpose of this research is to identify novel roles of kinesin families and/or subfamilies, with a particular focus on those that may function in the cilia/flagella. Human KIF12 was investigated as a representative of Kinesin-16 whilst the roles of Kinesin-13 subfamilies A and C motors were investigated using the kinesin subfamily members found in Trypanosoma brucei. An inducible system of ciliogenesis in IMCD3 cells was sought to allow investigation into the difference in KIF12 localisation and expression before and after ciliogenesis occurred. Induction of ciliogenesis in IMCD3 cells was unsuccessful with no significant change in the percentage of ciliated cells post-serum starvation and/or contact inhibition. To characterise KIF12-microtubule interactions in vitro, the human RefSeq reference standard KIF12 (rsKif12) sequence was used. After multiple failed attempts to express and purify rsKif12, sequence analysis showed rsKif12 lacks nucleotide-binding motifs conserved across the kinesin superfamily. To determine the KIF12 major splice variant, RNA-sequencing data and sequence alignments of KIF12 homologues were used. kif12ΔPPGGG, harbouring a five amino acid deletion that reduced polycystic kidney disease severity in mice, and KIF12 motor domain only samples were also determined. Having determined the correct major splice variant of KIF12, several expression constructs were created to find a soluble version of KIF12 as well as kif12MD and kif12ΔPPGGG. Expressed KIF12, kif12MD and kif12ΔPPGGG were tagged individually with 6x His or 6x His and GFP at either the N- or C-terminus. Only kif12MD tagged with a C-terminal GFP and 6x His was soluble. T. brucei Kinesin-13s Kin13-1, -3 (both 13A) and -6 (13C) interactions with microtubules were observed in vitro. Kin13-6 does not significantly change microtubule dynamics in vitro. This suggests that Kinesin-13Cs do not function in microtubule regulation. Kin13-3 depolymerises microtubules, consistent with the functions of other Kinesin-13A members. Kin13-1 controls microtubule length in a novel manner by cleaving at the microtubule lattice. Kin13-1 cleaving activity has revealed a possible means of regulating the mitotic spindle, and thus chromosome segregation, which was previously unidentified.